It's a new day : Microsoft's Office 2007 launch campaign - Sawhney, Mohanbir S.; Waikar, Sachin ([London] : SAGE, 2016)
Microsoft's Office team was developing the marketing communication plan for its new product, Office 2007. Office was a very mature product and several versions of the product had been introduced over more than 20 years. As such, the new version had to overcome the consumer perception that the versions of Microsoft Office that they already have are 'good enough' for them. The Office 2007 marketing team has come up with a two-step campaign strategy that sought to first create awareness and intrigue using traditional media, followed by the heavy use of digital media to get consumers to experience the product through different types of 'digital experiences.' The team needs to decide how much of its advertising spending it should shift from traditional media to digital.
Originally Published in: Sawhney, M., & Waikar, S. (2009). It's a New Day: Microsoft's Office 2007 Launch Campaign. 5-409-756. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 29, 2016).
Keywords: elektronické knihy; electronic books; Microsoft Corporation; Sales management -- Case studies; New products -- Case studies